OC-080 Reduced circulating FGF19 levels are associated with symptoms of diarrhoea in crohn's disease. (28th May 2012) - Nolan, J D; Johnston, I; Dew, T; Pattni, S; Orchard, T; Walters, J R
Abstract : Introduction: FGF19 is a polypeptide hormone produced in the ileum which inhibits hepatic synthesis of bile acid and is thought to have roles in regulation of bile acid pool size and in clinical conditions of diarrhoea. Fasting serum levels of FGF19 are reduced in patients with Crohn's disease (CD) involving the ileum and also in patients with CD and ileal resections (IR). Aims: To investigate the relationship between serum FGF19 and disease activity in CD and length of ileal resection. Methods: Blood samples were taken prospectively from patients after an overnight fast in 40 patients with Crohn's disease (24 non resected and 16 with previous IR), 19 healthy controls and 75 disease controls with SeHCAT negative chronic idiopathic diarrhoea. In 9 IR patients clinical records were available to establish the precise length of ileum resected. Disease activity was assessed by Harvey-Bradshaw Index (HBI). Diarrhoea was defined as stool frequency ≥3, Bristol stool chart ≥6. Serum FGF19 was measured by ELISA and data are expressed as medians and ranges. Nonparametric statistical tests (Mann–Whitney and Spearman rank correlations) were used. Results: Median levels of FGF19 were significantly lower in patients with non-resected CD (114 pg/ml, 3–339) compared to healthy controls (231 pg/ml, 74–655, p=0.002 and 0.005 respectively). Patients with previous IR (71 pg/ml, 17–152) had significantly lower levels than non-resected CD (p = 0.02). Out of 15 patients with non resected CD with ileal or ileo-colonic disease, eight had active disease (HBI>4) and had further radiological or endoscopic assessment of the ileum: four with symptomatic strictures had significantly higher FGF19 levels (328 pg/ml, 178–339) compared to the inactive patients (118 pg/ml, 46–256, p=0.04). Conversely, four with non-obstructive ileal inflammation had significantly lower FGF19 levels (33 pg/ml, 3–59) than inactive patients (p = 0.01) and this group had the lowest observed levels of FGF19. Six non resected CD with diarrhoea had significantly lower levels of FGF19 (86 pg/ml, 30–169) compared to the diarrhoea controls (246 pg/ml, 72–1000, p=<0.0001). In nine IR patients an inverse correlation between FGF19 levels and resection length was observed ( r= −0.81, p 0.01). Conclusion: Fasting serum levels of FGF19 are significantly reduced by IR or non obstructive ileal inflammation. Symptoms of diarrhoea in CD are associated with low levels of FGF19 and an inverse correlation is found between FGF19 and the length of previous ileal resections. Competing interests: None declared.